How to use gamified dashboards and learning analytics for providing immediate student feedback and performance tracking in higher education - de Freitas, S.; Gibson, David; Alvarez, V.; Irving, L.; Charleer, S.; Verbert, K. (2017)
With the wide use of the Internet and digital data sources, there has been a recent emergence of easy access to student data through learning analytics within learning management systems (LMS), grade data through student information systems (SIS) and broader sector data through benchmarking metrics and standards. With it has come the potential for greater capabilities for improving student performance through immediate feedback. Current literature considers the role of dashboards for student performance and feedback, but few papers consider the efficacy of fast feedback to students or other ways that information can be fed back to learners. In this paper, we consider the work done by three leading groups addressing the impact of gamification in university education, with a specific focus on how data is presented to the learner, that is using elements such as points, levelling up, narrative and progression to scaffold learning and provide increases in student motivation, engagement, satisfaction, retention and performance enhancements.